2004
DOI: 10.1113/expphysiol.2004.027243
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of prolactin, ANPergic, oxytocinergic and adrenal systems in response to extracellular volume expansion in rats

Abstract: The present study evaluated the effect of acute extracellular volume expansion (EVE) induced by intravenous injection of isotonic (0.15 M NaCl) or hypertonic saline (0.3 M NaCl) on prolactin, corticosterone, vasopressin, oxytocin and atrial natriuretic peptide (ANP) secretion. Male Wistar rats were treated with bromocriptine, sulpiride or dexamethasone. After isotonic and hypertonic EVE, the control group showed a significant increase in the plasma concentrations of prolactin, corticosterone, ANP and oxytocin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…On the other hand, rats submitted to hypertonic (1.8% NaCl) BVE presented increased plasma levels of AVP, OT and ANP in order to promote water reabsorption and renal sodium excretion (32)(33)(34).…”
Section: Effects Of Glucocorticoids On Neurohypophyseal Hormone Secrementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, rats submitted to hypertonic (1.8% NaCl) BVE presented increased plasma levels of AVP, OT and ANP in order to promote water reabsorption and renal sodium excretion (32)(33)(34).…”
Section: Effects Of Glucocorticoids On Neurohypophyseal Hormone Secrementioning
confidence: 99%
“…In 2004, Durlo et al (33) reported the first evidence for the participation of the HPA axis in hormone secretion induced by BVE in rats. These investigators reported that both hypervolemia and hyperosmolality increased plasma corticosterone concentrations, an event also known to occur in response to other types of stress, such as forced swimming, immobilization and hypoglycemia (35).…”
Section: Effects Of Glucocorticoids On Neurohypophyseal Hormone Secrementioning
confidence: 99%
“…Although AVP induces prolactin release in vivo (37), we did not observe changes in plasma AVP throughout the time course after ADX surgery (24), suggesting that this peptide might not have a role in prolactin se cretion in this experimental model. We and others have shown an increase in plasma PRL induced by increased water and salt ingestion or after hypertonic EVE infu sion (21,38). However, the increase in PRL and OT levels after isotonic or hypertonic EVE were blocked by glucocorticoid treatment.…”
Section: Discussionmentioning
confidence: 60%
“…We have previously studied the effect of acute extracellular volume expansion by intravenous injection of isotonic or hypertonic saline on the secre tion of prolactin, corticosterone, vasopressin, oxytocin, and atrial natriuretic peptide. We demonstrated that the increment in prolactin and oxytocin was blocked by the inhibition of the hypothalamuspituitaryadrenal (HPA) axis by dexamethasone (21). Therefore, pro lactin and oxytocin responses induced by isotonic or hypertonic extracellular volume expansion are likely to be modulated by the HPA axis.…”
mentioning
confidence: 96%
“…Accordingly, it has been demonstrated that high doses of dexamethasone can inhibit OT but not AVP secretion in response to hypertonic extracellular volume expansion (Durlo et al, 2004;Ruginsk et al, 2007) and central cholinergic, angiotensinergic and osmotic stimulation (Lauand et al, 2007). These effects were also correlated with immunohistochemical data, showing that the magnocellular neurons of the PVN and SON are inhibited by dexamethasone administration (Ruginsk et al, 2007).…”
Section: Endocannabinoids and The Control Of Hydromineral Homeostasismentioning
confidence: 99%